Carcass and meat characteristics of crossbred steers submitted to different nutritional strategies at growing and finishing phases - Rezende,Pedro Leonardo de Paula (2012)
This study was carried out to evaluate the effects of different nutritional strategies at growing and finishing phases on carcass and meat characteristics from 24 crossbred steers predominatly Holstein, slaughtered at 15 months of age and with 395.00kg of body weight. At the growing phase, the animals were maintained on Brachiaria brizantha pasture with two levels of supplementation in amounts equivalent to 0.5 or 1.0% of body weight. Subsequently, the animals were finished in feedlot with diets composed of 50 or 80% of concentrate. The high level of the concentrate at the finishing phase increased significantly (P<0.05) the hot carcass yield (50.16 vs. 48.62%). The lowest level of supplementation at the growing phase resulted in higher (P<0.05) percentage of carcass fat (25.61 vs. 23.39%) but it did not influence the percentage of muscle and bone. The high level of supplementation at the growing phase provided higher (p<0.05) meat tenderness, required less shear force (4.72 vs. 6.66kg cm-3) and lighter red meat (3.88 vs 2.89 points). The high feeding level during the growing phase was more interesting because it affected positively some important carcass and meat characteristics, especially tenderness.